Aplikasi Pengolahan Data Jemaat pada Gereja Kristus Yesus Kuta Bali menggunakan Framework Codeigniter - Ayu Nila Dewi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
The data processing system is a method of manipulating data into information that helps to increase the productivity of human activities. At present, the Gereja Kristus Yesus (GKY) Kuta Bali has used a computerized system based on Microsoft Office Word to manage congregational data, baptism data, marriage data, attendance data, and other ecclesiastical activities. However, in the process of managing the data, there are still some shortcomings including the data being managed in a conventional way which is relatively slow and there are difficulties in accessing the data because the data is only stored on certain media. In the dissemination of information such as worship schedules, Church activities, and other worship routines still use print media which are currently ineffective because printing worship services certainly require considerable operational funds and the scope of dissemination of the news is still relatively ineffective. Therefore, a system was developed to manage congregational data using several plannings and design concepts in the form of system analysis, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and the concept of Model View Controller (MVC). The Codeigniter Framework and Black Box Testing were used in developing this data management system apps for the GKY Kuta Bali`s congregation. The results shows that the data processing application of Gereja Kristus Yesus in Kuta Bali using Framework Codeigniter, scored by User Acceptance Testing test with an average of 4.20 in a good category and percentage of 84% in the very good category.